Rag painting everything you need to know for painting mottled-color faux finishes! ([U.S.A.] Faux Fun, Inc., 2004)
"You will learn several different types of rag painting techniques along with how to create other mottled finishes. Your host, Barbara, will also paint for the first time with a few rag-painting rollers amde available on the market. You will learn how one might work with these tools and if they are useful for creating rag-type finishes. In addition, Barbara will also show you examples of common mistakes people make when they are learning rag painting. She will show you why the problems happen, how to avoid them and how to fix the mistakes or work with them if they do occur. This tape is an excellent tool for the beginner faux painter. Simply learn everything you need to know to make rag painting look great"--in container.
DVD
Instructed by Barbara Wurden.
Keywords: Texture painting; Interior decoration; Finishes and finishing